Modelling and Finite Element Simulation of a Surface Acoustic Wave Driven Linear Motor. (2016) - Behera, Basudeba; Nemade, Harshal B.
Abstract: The paper presents modeling and finite element simulation of a surface acoustic wave (SAW) linear motor. A SAW linear motor works on the principle of friction drive provided by SAW propagating on a piezoelectric stator. The SAW motor comprises of a cubical slider driven by Rayleigh wave generated on a piezoelectric substrate using an interdigital transducer (IDT) fabricated on the stator. In the study, a lithium niobate piezoelectric substrate is used as the stator on which aluminum IDTs are fabricated at the two edges and a cuboid slider is placed in the path of SAW propagation along with a preload. The characteristics such as displacement, velocity and forces acting on the slider for different amplitudes of wave excitations are studied. The slider in the SAW motor can move both in forward and reverse directions and the motor attains a saturated velocity with the continuous wave excitation.